Modern Views in The Treatment of Mandibular Fractures (Progress Annals: Journal of Progressive Research, 2023)
In recent decades, the problem of mandibular fractures in trauma patients has become more relevant [1,2]. Against the background of industrialization of society, increase in traffic accidents, human and industrial accidents and public crimes, specialists of various specialties appear: surgeons, traumatologists, neurosurgeons, resuscitators and maxillofacial joint injuries. surgeons [3-6]. Surgical planning and choice of treatment. In cases where bite and occlusion are possible, conservative tactics can be used.